VIOLATIONS OF NEUROHUMORAL REGULATION OF CARDIAC ACTIVITY WHEN THE ARRHYTHMIAS OF VARIOUS ORIGINS - A. D. Bagmet; C. A. Stepanov; T. I. Stepanova; T. V. Tautina; E. A. Nedoruba (Медицинский вестник Юга России, 2015)
Purpose: to study the changes in psychological status, autonomic nervous system, as well as their relationship to the level of biogenic amines blood arrhythmias of various types and origins on the background of a combined treatment of anti-arrhythmic and psychotropic drugs.Materials and methods: surveyed, 95 patients (mean age of 45,2 +1,24 years), 42 men and 53 women with ekstrasystolichniy fibrillation, paroxysmal supraventricular tachycardia, atrial fibrillation on the background of coronary artery disease and vegetative dysfunction. Psychological testing conducted scales anxiety of Spilberger, depression Tsung, Hamilton, test RESINS, the content of biogenic amines in the serum were determined using a sensitive method in the sample.Results: the revealed disorders of autonomic balance, increased levels of anxiety, depression, poorer quality of life, reducing the protective functions of the CRL of the body.Summary: combined therapy, including activators SLS had a more pronounced antiarrhythmic effect, contributed to the stabilization of the ANS, and resolved the levels of biogenic amines is more effective than on the background of basic therapy.